Innate and adaptive immune cell subsets as risk factors for coronary heart disease in two population-based cohorts. (May 2020) - Olson, Nels C.; Sitlani, Colleen M.; Doyle, Margaret F.; Huber, Sally A.; Landay, Alan L.; Tracy, Russell P.; Psaty, Bruce M.; Delaney, Joseph A.
Abstract: Background and aims: Cell-mediated immunity is implicated in atherosclerosis. We evaluated whether innate and adaptive immune cell subsets in peripheral blood are risk factors for coronary heart disease. Methods: A nested case-cohort study (n = 2155) was performed within the Multi-Ethnic Study of Atherosclerosis (MESA) and the Cardiovascular Health Study (CHS). Cases of incident myocardial infarction (MI) and incident angina (n = 880 total cases) were compared with a cohort random sample (n = 1275). Immune cell phenotypes (n = 34, including CD14 + monocytes, natural killer cells, γδ T cells, CD4 +, CD8 + and CD19 + lymphocyte subsets) were measured from cryopreserved cells by flow cytometry. Cox proportional hazards models with adjustment for cardiovascular disease risk factors were used to evaluate associations of cell phenotypes with incident MI and a composite phenotype of incident MI or incident angina (MI-angina) over a median 9.3 years of follow-up. Th1, Th2, Th17, T regulatory (CD4 + CD25 + CD127 - ), naive (CD4 + CD45RA + ), memory (CD4 + CD45RO + ), and CD4 + CD28 − cells were specified as primary hypotheses. In secondary analyses, 27 additional cell phenotypes were investigated. Results: After correction for multiple testing, there were no statistically significant associations of CD4 + naive, memory, CD28 −, or T helper cell subsets with MI or MI-angina in MESA, CHS, or combined-cohort meta analyses. Null associations were also observed for monocyte subsets, natural killer cells, γδ T cells, CD19 + B cell and differentiated CD4 + and CD8 + cell subsets. Conclusions: The proportions of peripheral blood monocyte and lymphocyte subsets are not strongly related to the future occurrence of MI or angina in adults free of autoimmune disease. Graphical abstract: Image 1 Highlights: Cell-mediated immunity is established in animal models of atherosclerosis. Unclear if immune cell levels in blood are risk factors for future coronary events. CD4 + and CD8 + T cells were not related to incident myocardial infarction or angina. Monocytes, innate lymphocytes, and B cells were not related to coronary risk. Blood lymphocytes and monocytes may have limited utility as cardiovascular disease (CVD) biomarkers.